THE ROLE OF E-COMMERCE AND PRODUCT INNOVATION ON MSME PERFORMANCE - Sugito Sugito (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2024)
The purpose of this study is to determine the role of e-commerce and product innovation on the performance of MSMEs. Using literature and field research design. The information presented in this study was sourced from primary data and secondary data obtained by distributing questionnaires, conducting interviews and documentation to business owners. The data analysis used in this study is normality test, qualitative descriptive analysis, and quantitative descriptive analysis using the help of the SPSS program. The research population is 37 businesses engaged in fashion in Siantar Marimbun District. The results showed that there is a positive and significant influence between e-commerce and product innovation on MSME performance both simultaneously and partially and there is a strong relationship between e-commerce and product innovation with MSME performance. Then the high and low performance of MSMEs can be explained by e-commerce and product innovatio